Medical and Social Transformations in an Aging World - Kaufman, Sharon R. (Social Determinants of Health, 2017)
How do we know and live old age today? What does it mean to be old in a time of the promise of high-tech medical interventions? Anthropologists and sociologists address the phenomenon of growing old both as experienced by individuals and their families and by the ways in which older lives are embedded in social, historical and political contexts. In recent decades a multitude of factors ensure that the very ideas of ‘aging’ and ‘health’ in late life are being transformed. As a result many social scientists have turned their attention to global developments in the spread of biomedical knowledge, the impacts of high-tech interventions on the practice of medicine in an aging world and shifting societal expectations about longevity.